m6A Methylated Long Noncoding RNA LOC339803 Regulates Intestinal Inflammatory Response - Ane Olazagoitia‐Garmendia; Henar Rojas‐Márquez; Maialen Sebastian‐delaCruz; Aloña Agirre‐Lizaso; Anne Ochoa; Luis Manuel Mendoza‐Gomez; Maria J Perugorria; Luis Bujanda; Alain Huerta Madrigal; Izortze Santin; Ainara Castellanos‐Rubio (Advanced Science, 2024)
Abstract Cytokine mediated sustained inflammation increases the risk to develop different complex chronic inflammatory diseases, but the implicated mechanisms remain unclear. Increasing evidence shows that long noncoding RNAs (lncRNAs) play key roles in the pathogenesis of inflammatory disorders, while inflammation associated variants are described to affect their function or essential RNA modifications as N6‐methyladenosine (m6A) methylation, increasing predisposition to inflammatory diseases. Here, the functional implication of the intestinal inflammation associated lncRNA LOC339803 in the production of cytokines by intestinal epithelial cells is described. Allele‐specific m6A methylation is found to affect YTHDC1 mediated protein binding affinity. LOC339803‐YTHDC1 interaction dictates chromatin localization of LOC339803 ultimately inducing the expression of NFκB mediated proinflammatory cytokines and contributing to the development of intestinal inflammation. These findings are confirmed using human intestinal biopsy samples from different intestinal inflammatory conditions and controls. Additionally, it is demonstrated that LOC339803 targeting can be a useful strategy for the amelioration of intestinal inflammation in vitro and ex vivo. Overall, the results support the importance of the methylated LOC339803 lncRNA as a mediator of intestinal inflammation, explaining genetic susceptibility and presenting this lncRNA as a potential novel therapeutic target for the treatment of inflammatory intestinal disorders.